Nutritional status of school children aged 6-10 years old in Selangor - Kassim, siah; Mohamed Zainuddin, Norzila; Ab Rahman, Jamalludin; Zainal, Ramli; Abdullah, Ahmad Fadzil; Abdul Wahab, Norrashidah; Awang, Rusanida; Latif, Hasniah; Hussain, Shamsinah (Malaysian Paediatrics Association, 2010)
Objective: To assess nutritional status of school children aged 6 to 10 years old in Selangor. Method: All school children in Standard 1, 2, 3 and 4 from randomly selected seven primary schools in Selangor were given questionnaire forms. Children with parental consent underwent physical examination by the research team. Data collected include demographic, weight, height, biceps skin-fold thickness, neck circumference and waist circumference. Nutritional status was categorized following WHO 2006 growth chart standard. Results: Total 4434 school children aged 6-10 years old participated. Nutritional status of the school children was categorized into 6 groups i.e. very thin (1.5%), thin (6.6%), normal (67.3%), overweight (12.1 %), obese (8.1%) and very obese (3.7%). About 11% of the rural school children were within thin and very thin compared to urban school children 6.5%. However, the distribution of overweight, obese and very obese school children in rural and urban schools was similar i.e. 24%. Conclusion: The increasing trend of overweight and obesity among adult was also seen in school children aged 6-10 years old in Selangor.